EVALUASI KEBIJAKAN PEMERINTAH DAERAH KOTA PEKANBARU DALAM PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA TAHUN 2018-2019 - Kiki Pebrianti; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Street vendors or commonly called PKL are a group of traders who sell their wares on the sides of public roads, sidewalks, which are far from being neat and clean. The regulations governing the management of street vendors are contained in Regional Regulation Number 11 of 2001 concerning the arrangement and development of street vendors. The city of Pekanbaru has 6 traditional markets and what is of concern is the Sukaramai traditional market or what is called the Agus Salim market, because the market has experienced an increase in street vendors from 2018-2019. The Pekanbaru City Trade and Industry Office has made efforts and is also working with the Pekanbaru City Civil Service Unit to control traders selling along Jalan Agus Salim, but after the control was carried out the traders returned to their original selling places, so problems related to street vendors continued to occur. The method used in this study is qualitative, the data sources used in this study include primary data and secondary data, the research location was carried out at the Department of Industry and Trade in the Market Sector. The research informants in this study were the Head of the Market Sector, the Head of the Civil Service Police Unit Investigators, Traders and Buyers. The theoretical concept used by researchers is the policy evaluation theory. This study uses a qualitative research method, data collection techniques used are interviews and documentation. The results of the study, that the evaluation of the policy of Regional Regulation Number 11 of 2001 concerning the management and development of street vendors by the Industry and Trade Office in the Pasa Sector has not been maximized, which is caused by several factors, namely the lack of human resources in the Market Sector, lack of a budget that supports the construction and provision of facilities markets, lack of coordination between sub-districts, sub-districts and other relevant agencies. Keywords: Policy Evaluation, Performance, Management and Development